Best Paper Selection (Yearbook of Medical Informatics, 2017)
Arnold CW, Wallace WD, Chen S, Oh A, Abtin F, Genshaft S, Binder S, Aberle D, Enzmann D. RadPath: A web-based system for integrating and correlating radiology and pathology findings during cancer diagnosis. Acad Radiol 2016 Jan;23(1):90-100 http://escholarship.org/uc/item/22x4021qHravnak M, Chen L, Dubrawski A, Bose E, Clermont G, Pinsky MR. Real alerts and artifact classification in archived multi-signal vital sign monitoring data: implications for mining big data. J Clin Monit Comput 2016 Dec;30(6):875-88 https://link.springer.com/article/10.1007%2Fs10877-015-9788-2Kalpathy-Cramer J, Zhao B, Goldgof D, Gu Y, Wang X, Yang H, Tan Y, Gillies R, Napel S. A comparison of lung nodule segmentation algorithms: methods and results from a multi-institutional study. J Digit Imaging 2016 Aug;29(4):476-87 https://www.ncbi.nlm.nih.gov/pmc/articles/PMC4942386/Moss TJ, Lake DE, Calland JF, Enfield KB, Delos JB, Fairchild KD, Moorman JR. Signatures of subacute potentially catastrophic illness in the ICU: model development and validation. Crit Care Med 2016 Sep;44(9):1639-48 https://insights.ovid.com/pubmed?pmid=27452809Petousis P, Han SX, Aberle D, Bui AA. Prediction of lung cancer incidence on the low-dose computed tomography arm of the National Lung Screening Trial: A dynamic Bayesian network. Artif Intell Med 2016 Sep;72:42-55 https://linkinghub.elsevier.com/retrieve/pii/S0933-3657(16)30106-3Springer DB, Tarassenko L, Clifford GD. Logistic regression-HSMM-based heart sound segmentation. IEEE Trans Biomed Eng 2016 Apr;63(4):822-32 http://ieeexplore.ieee.org/document/7234876/